The Health Benefits of Soybeans: A Review of the Nutritional and Therapeutic Effects of Soy Protein, Isoflavones, and Bioactive Peptides - Alleza, Zikhatu Amina; Arshad, Maiza; Sikander, Maheen; Abid, Futrus; Kanwal, Shumaila; Habib, Hafiz Faisal; Khalid, Momina; Akhtar, Adeel; Mahmood, Waqas; Najeeb, Mehak; Zulqarnain (Indus Journal of Bioscience Research, 2025)
It’s a leguminous crop belong to family Fabaceae. From centuries Soybean [Glycine max (L.)] is used as a food in China and south Asia .in 1980 Japan recognized it as a functional food. It gives globally, industrial and economic importance due to high protein content, beneficial fat so used as alternative to animal protein. It classified on protein contain basis soy flour, concentrates, isolates. On dry protein content basis soya isolates are purest form of (>90%) protein that’s why it considers for soy-based infant formula, also show its effect in health improvement and exercise performance. Its products are given in diversity form like including infant formulas (for lactose intolerance), Cheese, beverages, miso, tempeh, tofu, salami, and vegetarian meat replacements in powered Form it’s available. Its bioactive peptide present physiologically activity prevent chronic diseases, also have therapeutic effect on health like lower the risk of CVD, breast and prostate cancer, promote bone health, maintain muscles and relief post-menopausal symptoms, improve renal function, relieve depressed symptoms, and promote skin health.